Thermoeconomic analysis of a standalone solar hydrogen system with hybrid energy storage. (26th July 2019) - Jafari, Moharrm; Armaghan, Davoud; Seyed Mahmoudi, S.M.; Chitsaz, Ata
Abstract: A comprehensive thermoeconomic analysis is presented for a novel integrated solar hydrogen energy system for standalone operation. The proposed system includes a solar PVT module (photovoltaic thermal), a FC (Fuel cell) and a battery to meet the electrical load demand and domestic hot water over a year. The PVT component works as a primary energy source converting solar energy into electricity and heat. The excess electrical energy and hot water produced by PVT are consumed for producing hydrogen, which can be stored. The generated hydrogen is fed to the fuel cell to produce electricity and water to satisfy the demand. The proposed system is convenient for different seasons of the year because in all time, produced power satisfy the demand. The first and second laws of thermodynamics are used to evaluate the performance of each component and the overall system. Economic assessment of this system is also conducted considering the net present cost, and the system performance is optimized based on this parameter. The overall electrical efficiency of the system is obtained as 9% and the levelized cost of electricity is determined as $ 0.286/kWh. For a steady operation of system, integrating a battery system is convenient when solar energy is not available for a short term. When there is a longer-term shortage of solar radiation, up to 8 days, the electricity can be supplied by utilizing the hydrogen storage system. Highlights: A novel integrated solar hydrogen system for standalone operation is proposed. Highest exergy destruction occurs at the PVT component. Levelized cost of electricity for the ISHES is obtained as $ 0.286/kWh. Autonomy of 8 days for hydrogen storage is the most desirable option economically.